2014
DOI: 10.5604/15093492.1119616
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Cultural Adaptation of the Polish Version of the Disabilities of the Arm, Shoulder and Hand (DASH) and QuickDASH Questionnaires

Abstract: 1. The translation and cultural adaptation led to the development of the official Polish versions of the DASH and QuickDASH questionnaires. 2. Although we have provided some evidence of content validity, additional testing for the retention of psychometric properties of the translated questionnaire is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The study used the following research instruments (translated into Polish): PROMIS® Pain Intensity [19][20][21][22][23][24][25][26] (Short Form 3a); PROMIS® upper extremity [17,27], and the widely used DASH [16,28]. The PROMIS® Pain Intensity (Short Form 3a v1) instrument was developed to assess the intensity of perceived pain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study used the following research instruments (translated into Polish): PROMIS® Pain Intensity [19][20][21][22][23][24][25][26] (Short Form 3a); PROMIS® upper extremity [17,27], and the widely used DASH [16,28]. The PROMIS® Pain Intensity (Short Form 3a v1) instrument was developed to assess the intensity of perceived pain.…”
Section: Methodsmentioning
confidence: 99%
“…The aims of this study were to determine the environmental conditions for the occurrence of CTS in a non-industrial area, and patient-reported outcomes after a single postoperative outpatient clinic visit using the Disability of Arm Shoulder and Hand (DASH) [16], and Patient-Reported Outcomes Measurement Information System (PROMIS®) Upper Extremity and SF 3a questionnaires, and compare the results obtained using these two outcome instruments [17].…”
Section: Objectivesmentioning
confidence: 99%
“…A large number of measurement tools for evaluating patients with shoulder problems are available for assessing symptoms, functioning and quality of life, the majority of which were developed in English-speaking countries. Some of those questionnaires available are: the Western Ontario Shoulder Instability Index (WOSI) [ 6 ] and the Shoulder Instability Questionnaire (SIQ) [ 7 ], the Western Ontario Osteoarthritis of the Shoulder Index (WOOS) [ 8 ], the Western Ontario Rotator Cuff Index (WORC) [ 9 ] and the Rotator Cuff Quality of Life Index (RC-QOL) [ 10 ], the Disabilities of the Arm, Shoulder and Hand Questionnaire (DASH) [ 11 ] and its shortened version - QuickDASH [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…An integral part of the questionnaire is two optional modules, "Work" and "Sport/Playing an instrument." For the purpose of the conducted research, the optional module "Work" was used [7]. Calculations were performed in accordance with the recommendations of the Institute for Work & Health [8].…”
Section: Methodsmentioning
confidence: 99%